2021
DOI: 10.1186/s12913-021-06469-2
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of REAGERA-P, a new questionnaire to evaluate health care provider preparedness to identify and manage elder abuse

Abstract: Background Elder abuse is prevalent and associated with morbidity but often goes unnoticed in health care. Research on the health care response to victims calls for valid measurements. This article describes the development and validation of a questionnaire to evaluate health care provider preparedness to care for older adults subjected to abuse, the REAGERA-P (Responding to Elder Abuse in GERiAtric Care – Provider questionnaire). Method REAGERA-P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Data will be collected with the REAGERA-P (Responding to Elder Abuse in GERiAtric care–Provider questionnaire). It is a validated instrument 39 that can be used to measure healthcare providers’ preparedness to ask older patients questions about abuse and manage the response. The items of relevance for this study are presented in table 1 and the complete REAGERA-P as online supplemental file 1 .…”
Section: Methods and Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Data will be collected with the REAGERA-P (Responding to Elder Abuse in GERiAtric care–Provider questionnaire). It is a validated instrument 39 that can be used to measure healthcare providers’ preparedness to ask older patients questions about abuse and manage the response. The items of relevance for this study are presented in table 1 and the complete REAGERA-P as online supplemental file 1 .…”
Section: Methods and Analysismentioning
confidence: 99%
“…Construct and convergent validity of the REAGERA-P was previously tested in a sample of 154 healthcare providers by using factor analysis, test of internal consistency and by investigating associations between relevant variables. 39 Based on lessons learnt in that data collection, the instrument was further improved and has later been used to evaluate a pilot study of the current educational intervention. 26 In the pilot study, a possible ceiling effect was found for two items about sense of responsibility and therefore the response categories were modified for the current study, that is, changed from a 4-point ordinal scale to a 6-point ordinal scale.…”
Section: Methods and Analysismentioning
confidence: 99%
See 3 more Smart Citations